Teacher Opinions on the Applicability of the 2017 Secondary Education English Curriculum Based on the Blended Learning Approach - Eda Aksoy Tosun; F. Belgin Özaydınlı (Anı Publishing, 2020)
The aim of this study is to determine the views of teachers about the applicability of the 2017 Secondary Education English Curriculum based on blended learning. Phenomenology, a qualitative research design, a semi-structured interview form developed by the researcher and content analysis, one of the data analysis methods, were used in the study. In the study, 20 English teachers from Anatolian high schools in Kocaeli were interviewed. The findings were evaluated in view of the readiness of the teachers for the curriculum, of the practices carried out by the teachers in the courses, of student readiness and technological competence, and of institutional infrastructure and expert support. Despite the positive opinions of teachers toward the blended learning approach, the study concludes that a number of obstacles are encountered in the implementation of the 2017 English Curriculum due to several reasons such as; lack of necessary in-service training for teachers on blended learning,  lack of appropriate content in Education Informatics Network (EBA) and Dynamic and Education (DynEd), low level of technological literacy of students, and the inadequacy of institutions in providing services like internet connection, computer supply and expert support.